Case Report: Recurrent Keloid Excision with Tension Reduction Suture and Adjuvant Closed Incision Negative Pressure Wound Therapy - Ananda Rahmadanti Perdanakusuma; David Sontani Perdanakusuma (International Medical Journal Corp. Ltd, 2025)
Background: Keloid management presents significant clinical challenges due to the very high recurrence rate after single surgical excision, reported to reach 50-100%. This failure is primarily caused by mechanical tension on the post-closure wound, which reactivates the fibroproliferative cascade. Closed Incision Negative Pressure Wound Therapy (ciNPWT) emerges as a promising adjuvant therapy because it directly targets this mechanical tension. This case report aims to present the effectiveness of a combination of excision, tension reduction sutures, and ciNPWT in high-risk recurrent keloids. Methods: A 16-year-old male patient with a recurrent keloid on the right upper arm underwent a wide excision procedure and tension reduction suture technique. After wound closure, a ciNPWT dressing was applied over the incision line and connected to a portable device. Continuous negative pressure therapy of −125 mmHg was maintained for 7 days post-operation. Results: The surgical procedure and post-operative care proceeded smoothly without complications such as infection or wound dehiscence. After 7 days, the surgical wound appeared clean and tightly closed with minimal edema. At the 3-month follow-up, the scar appeared calm, flat, and aesthetic, with no clinical signs of keloid recurrence. The patient reported high satisfaction and resolution of itching complaints. Discussion: The success of managing this case strongly validates the fundamental theory that mechanical tension is the primary trigger for keloid recurrence. The applied approach—through surgical excision followed by a tension reduction suture technique—directly targets this crucial factor. Furthermore, the application of ciNPWT as an adjuvant therapy functions as an effective external